The Effect of Lavender Essential Oil Aromatherapy on Reducing the Risk of Postpartum Blues Among Postpartum Mothers: A Quasi-Experimental Study - Hasniah Dina; Ari Nofitasari; Dedi Krismiadi; Yulli Fety; Wa Ode Aisa Zoahira (Jurnal Kesehatan Budi Luhur: Jurnal Ilmu-Ilmu Kesehatan Masyarakat, Keperawatan, dan Kebidanan, 2026)
The postpartum period is a phase of physical and psychological adaptation during which mothers are vulnerable to emotional disturbances, including postpartum blues. Non-pharmacological interventions such as lavender aromatherapy have been reported to promote relaxation and may help reduce anxiety and stress among postpartum mothers. This study aimed to determine the effect of lavender essential oil aromatherapy on reducing the risk of postpartum blues among mothers in the working area of the Lameuru Community Health Center. A quasi-experimental study with a pretest–posttest control group design was conducted. A total of 60 respondents were recruited using a total sampling technique and allocated to an intervention group (n = 30) and a control group (n = 30). The intervention group received lavender essential oil aromatherapy for 14 days, whereas the control group received standard postpartum care, including health education and routine postpartum services. The Edinburgh Postnatal Depression Scale (EPDS) was used to assess the risk of postpartum blues. Data were analyzed using the Wilcoxon signed-rank test and the Mann–Whitney U test. The median EPDS score in the intervention group decreased substantially from 14.00 (IQR: 12.75–15.00) at pretest to 7.00 (IQR: 6.00–8.25) at posttest, while the median EPDS score in the control group decreased from 14.00 (IQR: 13.00–15.00) at pretest to 12.00 (IQR: 11.00–13.00) at posttest. Between-group analysis demonstrated a statistically significant difference in EPDS score changes (p < 0.001). These findings indicate that lavender essential oil aromatherapy is more effective than standard postpartum care in reducing the risk of postpartum blues among postpartum mothers.